Peningkatan Kesadaran dan Kesiapsiagaan Siswa SD Negeri 2 Banda Aceh Terhadap Bencana Gempa Bumi - Amsir, Amsir; Salsabila, Rifa Salma; Hidayati, Dian Meutia (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
Earthquakes, a disaster that often occurs in Indonesia, are caused by the movement of tectonic plates. Indonesia is a region located at the meeting of three active plates, namely, Indo-Australian, Eurasian, and Pacific, which gives Indonesia a high level of vulnerability to earthquake disasters. Banda Aceh is one of Indonesia's regions with a high vulnerability to earthquake disasters, so awareness of disaster mitigation is needed early on. Children have a higher level of disaster vulnerability than adults because they can still not control and prepare themselves for disasters. One effort that can be made to increase children's knowledge about disaster mitigation is to conduct disaster outreach. The outreach aims to increase children's understanding of the dangers of earthquakes, evacuation steps, and first aid that must be carried out to reduce the impact of disasters. Socialization includes interactive presentations, discussions, and evaluations to measure students' understanding of disaster material. The sample for this socialization was 25 grade IV students and 31 grade VI elementary school students. Data collection will use tests in the form of questions about earthquakes to measure the results of students' knowledge of disaster mitigation and compare their understanding of class IV and class VI students. The results of the socialization show that the level of understanding of class VI students is higher in understanding the material provided; around 90% of class VI students and 82% of class IV students understand the material that has been provided; this number has increased from before the disaster socialization was carried out.